Estudo sobre o gerenciamento de resíduos sólidos industriais em uma indústria do segmento têxtil - Metidieri, Eduardo Nascimento (Universidade Federal de São Carlos, 2021)
The concern with solid waste has become an increasingly frequent topic of discussion in society. Inadequate disposal and environmental impacts generated by the industrial sector are being less and less tolerated by consumers. The textile sector has an expressive participation in the generation of solid waste and environmental impacts that, if not treated correctly, can cause irreversible damage to the environment. Thus, this work aims to study the management of solid waste from the manufacturing process of a textile industry, which produces articles for bed, table and bath, located in the city of Votorantim-SP. The applied methodology is based on an action research that will address in an organized manner activities that will make it possible to identify risks, quantify costs, establish and apply methods and raise stakeholder awareness of the importance of correct waste disposal. The results obtained through this work were the elaboration of the flowchart of the industrial production processes, the identification of the current waste disposal sites, the survey of the risks of inadequate disposal, the analysis of the failure modes and elaboration of the Failure Mode and Effects Analysis - FMEA, the indication of new points of disposal and selective collection, the preparation of a booklet on the correct disposal of waste and the assessment of electricity consumption. Finally, it is concluded that this research used tools for waste management and management, resulting in its complete implementation, favoring the mitigation of environmental impacts arising from the production process.
Study on the management of industrial solid waste in a textile industry
Keywords: Solid waste; Textile industry; Management; Environmental impact; Resíduos sólidos; Indústria têxtil; Gerenciamento; Impacto ambiental; ENGENHARIAS